The Principal's Strategy In Growing Participation Of The Education Aware Community - Abdul Goffar; Mohammad Bilutfikal khofi (At-Tarbiyat, 2021)
This research departs from the phenomenon of Nurul Huda Grujugan Kidul Bondowoso junior high school, namely the lack of community participation in education. This can be seen from the absence of infaq money or administrative payments from the student's guardians to the school, so education funds are minimal. This limited funding certainly has an impact on various fields of education management. This study describes the principal's strategy in fostering public interest in education. With this strategy, it is hoped that the public's interest in helping schools will grow. This study uses a qualitative research approach. In collecting data, researchers used interviews, observation, and documentation techniques. The study results found that the principal's strategy to foster public interest was carried out by; 1) building a good image in the community by carrying out religious activities; 2) providing opportunities for the community to participate in different ways according to their respective abilities and professions.